Can metal-tolerant endophytic biocontrol agents promote plant-growth under metal stress? - Sim, Carrie Siew Fang; Cheow, Yuen Lin; Ng, Si Ling; Ting, Adeline Su Yien (Acta Biologica Szegediensis, 2020)
Five metal-tolerant endophytic isolates (Bipolaris sp. LF7, Diaporthe miriciae LF9, Trichoderma asperellum LF11, Phomopsis asparagi LF15, Saccharicola bicolor LF22), with known metal-tolerance attributes and biocontrol activities against Ganoderma boninense, were tested for growth-promoting activities independent of (in vitro) and associated with plants (height, weight, root mass and stem circumference) (in vivo). Results revealed that metal-tolerant endophytes did not significantly render benefit to host plants as plant growth was compromised by the presence of metals. Lower production of indole-acetic acid (0.74-21.77 μg mL-1), siderophores (8.82-90.26%), and deaminase activities of 1-aminocyclopropane carboxylic acid (3.00-69.2 μmol mg protein-1 hr-1) were observed.